A Study of Differences in the Meaning of the Logos between John and Greek Literature - Kim, Sun Wook (2025)
The purpose of this article is to explore the concept of the Logos in John 1:1-18 and how it differs from Greek and Hellenistic philosophy and religious thought. While the term Logos was frequently used in these contexts, John’s understanding of it is unique and shaped by his Christological perspective. To demonstrate this, I examine the concepts of the Logos used by Heraclitus, Zeno, and Poimandres and discover how John’s understanding and use of the Logos differ from theirs. Although John borrowed the term to convey his theology to Hellenic readers, his Logos doctrine is distinct and centers on Jesus Christ as the incarnate person who is equal to God.
Keywords: Poimandres; Zeno; Heraclitus; John; Logos